MODEL PENGEMBANGAN ZAKAT PRODUKTIF DI LEMBAGA AMIL ZAKAT DAARUT TAUHIID PEDULI JAMBI (Studi Kasus Daarut Tauhiid The Hok Jambi, Kota Jambi) - Dicky Hendardi; Sucipto Sucipto; Addiarrahman Addiarrahman (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
In helping the muzzaki tithe in daruut tauhiid care Jambi and make it easier for muzakki to tithe in amil zakat institutions. the amil zakat institution cares Jambi can develop educational programs with the aim that the participants of the education program who cannot afford to go to school with the help of donations given by the muzakki. With the educational program at Daruut Tauhiid, the Daruud Tauhiid institution can develop the interests of the participants and develop the talents they have with the aim that the participants will help develop programs that exist at Daruut Tauhiid Care Jambi. The results of the study show that: (1) The strategy for collecting zakat funds carried out by the Jambi Branch of the Amil Zakat Daarut Tauhiid Peduli Institute is to optimize collection through digital channels online and offline. Using payment services owned by the institution and also cooperating with other institutions. Using payment services owned by the institution and also cooperating with other parties. (2) how the institution develops the assets that have been given by the muzakki to be developed in the programs that have been given by the muzakki. Using social media for documentation that has been carried out with the aim that the trust of people who give zakat is trustworthy if they give zakat at amil zakat daruut tauhiid institutions.